The Sentence Boundary Errors: Diagnosing the EFL Students’ Sentence-Level Inaccuracies in the EFL Writing Classrooms - Yalmiadi, Yalmiadi; Telaumbanua, Yohannes (Fakultas Sastra Universitas Ekasakti, 2024)
ABSTRACT The syntactic complexities of English sentence structures induced the EFL students’ sentence-level accuracies senseless. The Sentence’s Boundary Errors were, therefore, the major essences of this study. This study aimed at diagnosing the 2nd-year PNP ED students’ SBEs as the writers of English Paragraph Writing at the Writing II course. Qualitatively, both observation and documentation were the instruments of collecting the data while the 1984 Miles & Huberman’s Model and the 1973 Corder’s Clinical Elicitation were employed to analyse the data as regards the SBEs produced by the students. The findings designated that the major sources of the students’ SBEs were the subordinating clauses (noun, adverb and relative clauses), that-clauses, participle phrases, infinitive phrases, lonely verb phrases, afterthought, appositive fragments, fused sentences and comma splices. As a result, the SBEs flopped to communicate complete thoughts because they were grammatically incorrect; lacked a subject, a verb; the independent clauses ran together without properly using punctuation marks, conjunctions or transitions; and two or more independent clauses were purely joined by commas but failed to consider using conjunctions. In conclusion, the success of the EFL students in constructing sentences rests upon the knowledge of complex syntactic structures through transformational grammar. Keywords: SBEs; diagnosing; EFL students; sentence-level inaccuracies